2021
DOI: 10.1051/sicotj/2021006
|View full text |Cite
|
Sign up to set email alerts
|

Number of screws in the articular segment of distal humerus AO/OTA C-type fractures treated with open reduction internal fixation is associated with complication rate

Abstract: Introduction: Surgical treatment of distal humerus fractures can lead to numerous complications. Data suggest that the number of screws in the distal (articular) segment may be associated with complication rate. The purpose of this study is to evaluate the association between a number of screws in the distal segment and complication rate for surgical treatment of distal humerus fractures. We hypothesize that the number of screws in the articular segment of distal humerus AO/OTA C-type fractures treated with op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Stable fixation is of paramount importance for early mobilization [5,10,13]. The intraarticular level of the fracture should be fixed with as many screws as possible (at least three), which need to be inserted through the plate [3,14]. Although plate configuration seems to be more stable in biomechanical studies, than 90/90 fixation, this is not interpreted in vivo [9].…”
Section: Discussionmentioning
confidence: 99%
“…Stable fixation is of paramount importance for early mobilization [5,10,13]. The intraarticular level of the fracture should be fixed with as many screws as possible (at least three), which need to be inserted through the plate [3,14]. Although plate configuration seems to be more stable in biomechanical studies, than 90/90 fixation, this is not interpreted in vivo [9].…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that at least four long screws should be used to completely penetrate the distal end fragment from one side to the other. Grogan et al 8 showed that the use of ≤3 screws in distal humeral fractures was a significant risk factor for non-union. A biomechanical study revealed that the total number of screws was the most influential variable.…”
Section: Discussionmentioning
confidence: 99%
“…6 Another study reported that long oblique fracture patterns and obesity are prognostic factors for non-union. 7 Recent studies reported that the use of ≤3 screws for the fixation of the articular fragment in AO type C fractures, 8 and ORIF with tension band wiring 9 are significant risks for non-union. These studies included relatively small study populations, did not include comparison by fixation method and were conducted in single-center settings.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the articular fragments was checked under direct visualization or fluoroscopy guidance. Two vertical double plates (Trauson Jiangsu Medical Equipment Company, China) were used to definitively fix from lateral to medial side, with at least four screws in the articular fragments 19 . Fracture fixation stability and elbow range of motion were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Two vertical double plates (Trauson Jiangsu Medical Equipment Company, China) were used to definitively fix from lateral to medial side, with at least four screws in the articular fragments. 19 Fracture fixation stability and elbow range of motion were assessed. Lateral collateral ligamentous complex should be repaired with drill‐holes and a locking suture technique to prevent posterolateral rotatory instability in all cases.…”
Section: Methodsmentioning
confidence: 99%